Optimization of Bhabinkamtibmas Activities in the Context of Outreach for Students to Prevent Narcotics Abuse at the Bogor City Police - Hilda Safira Ayu Rulita Jati (Advances in Police Science Research Journal, 2021)
The background of this research is because there is still Narcotics Abuse among students in the Bogor City Police area. Therefore, the authors are interested in seeing the phenomenon that occurs and trying to link it with the implementation of Bhabinkamtibmas duties in counseling on drug abuse among students. So a research was carried out which aims to determine the description of the implementation of counseling by Bhabinkamtibmas, the factors that influence extension, as well as efforts to optimize Bhabinkamtibmas extension. The research conducted by the author was carried out in the city of Bogor, especially the Bogor City Police, using a qualitative approach, using field research research methods (field research), and using POAC management theory, communication theory, and crime prevention theory as well as management resource theory. This research is based on the Regulation of the Head of the National Police of the Republic of Indonesia Number 21 of 2007 concerning Guidance for Community Security and Order Counseling, which includes the management of the extension consisting of planning or preparation stages to controlling guidelines in analyzing extension activities by Bhabinkamtibmas to prevent narcotics abuse against students. The results showed that Bhabinkamtibmas work was in accordance with the SOP but there were still influencing factors, namely the facilities and infrastructure factors, human resource factors, and budget factors as well as students' legal awareness factors. Efforts that have been made use secondary crime prevention theory, namely a form of cooperation with internal and external Polri to get maximum results and as expected. The results of this study are expected to provide an overview of how to optimize extension activities by Bhabinkamtibmas, because the methods, techniques and utilization of all existing organizational resources are expected to be more able to reduce the level of narcotics abuse among students.